Post-analysis methods for lactate threshold depend on training intensity and aerobic capacity in runners. An experimental laboratory study - Fernandes, Tiago Lazzaretti; Nunes, Rômulo dos Santos Sobreira; Abad, Cesar Cavinato Cal; Silva, Andrea Clemente Baptista; Souza, Larissa Silva; Silva, Paulo Roberto Santos; Albuquerque, Cyro; Irigoyen, Maria Cláudia; Hernandez, Arnaldo José (São Paulo Medical Journal, 2016)
CONTEXT AND OBJECTIVE: This study aimed to evaluate different mathematical post-analysis methods of determining lactate threshold in highly and lowly trained endurance runners. DESIGN AND SETTING: Experimental laboratory study, in a tertiary-level public university hospital. METHOD: Twenty-seven male endurance runners were divided into two training load groups: lowly trained (frequency < 4 times per week, < 6 consecutive months, training velocity ≥ 5.0 min/km) and highly trained (frequency ≥ 4 times per week, ≥ 6 consecutive months, training velocity < 5.0 min/km). The subjects performed an incremental treadmill protocol, with 1 km/h increases at each subsequent 4-minute stage. Fingerprint blood-lactate analysis was performed at the end of each stage. The lactate threshold (i.e. the running velocity at which blood lactate levels began to exponentially increase) was measured using three different methods: increase in blood lactate of 1 mmol/l at stages (DT1), absolute 4 mmol/l blood lactate concentration (4 mmol), and the semi-log method (semi-log). ANOVA was used to compare different lactate threshold methods and training groups. RESULTS: Highly trained athletes showed significantly greater lactate thresholds than lowly trained runners, regardless of the calculation method used. When all the subject data were combined, DT1 and semilog were not different, while 4 mmol was significantly lower than the other two methods. These same trends were observed when comparing lactate threshold methods in the lowly trained group. However, 4 mmol was only significantly lower than DT1 in the highly trained group. CONCLUSION: The 4 mmol protocol did not show lactate threshold measurements comparable with DT1 and semi-log protocols among lowly trained athletes.